THE EFFECTIVENESS OF HERRINGBONE TECHNIQUE IN TEACHING READING COMPREHENSION AT VOCATIONAL HIGH SCHOOL - Trival Setyadik; Audi Yundayani; Suratinah Suratinah (SOSCIED, 2023)
An efficient method of reading comprehension instruction is required for students to comprehend a text. This study's objectives were to examine if the Herringbone technique helps teach reading comprehension to vocational high school students majoring in fisheries and to explain the students' perceptions of the technique. This study's sample comprised students from the fisheries aquaculture technology department at Sekolah Usaha Perikanan Menengah (SUPM) in Pontianak. This study utilized a mixed-methods research approach. The researcher obtained data from the students by pre-test and post-test, observation, questionnaire, and interview. The Herringbone approach significantly impacts reading comprehension, as determined by statistical analysis. This research also demonstrated that the Herringbone approach was 14% effective in improving students' reading comprehension. Then, based on the students' perceptions of the Herringbone technique, it can be concluded that the students have a positive perception of reading comprehension while utilizing the Herringbone technique and the 5W1H method. In other words, the herringbone method significantly enhances students' reading comprehension in vocational high schools.